2018
DOI: 10.1017/jfm.2018.495
|View full text |Cite
|
Sign up to set email alerts
|

Plane blast wave interaction with an elongated straight and inclined heat-generated inhomogeneity

Abstract: The unstable evolution of an elongated elliptically shaped inhomogeneity that is embedded in ambient air and aligned both normal and at an angle to an incident plane blast wave of impact Mach number 2.15 is investigated both experimentally and numerically. The elliptic inhomogeneities and the blast waves are generated using gas heating and exploding wire technique and their interaction is captured optically using shadowgraph method. While two symmetric counter-rotating vortices due to Richtmyer–Meshkov instabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…The facility is a compact, 2D blast wave generator with visual access constructed within the group recently. The details on its construction, operation and the visualization systems can be found in [24], as it is beyond the scope of this work. Figure 5 shows the shadowgraph images captured in the facility.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The facility is a compact, 2D blast wave generator with visual access constructed within the group recently. The details on its construction, operation and the visualization systems can be found in [24], as it is beyond the scope of this work. Figure 5 shows the shadowgraph images captured in the facility.…”
Section: Methodsmentioning
confidence: 99%
“…The basic idea of the scheme is to split the flux vector using artificial wave speeds that adjust the direction of wave propagation [27]. The numerical scheme has been tried, tested and validated on a variety of problems, with it consistently demonstrating good accuracy [22,[28][29][30][31]. The axisymmetric version of the code has been specifically utilized to study spherical implosion shocks [22] where it was validated against experimental data.…”
Section: Numerical Analysismentioning
confidence: 99%
“…Schlieren images of the shock-induced two successive slow/fast interface evolutions acquired from experiments and simulations are shown in figure 7( a – f ). The magnitude of the density gradient () field in the simulations is calculated as (Quirk & Karni 1996; Sembian, Liverts & Apazidis 2018) Taking the L50-IP case as an example, the deformations of the two interfaces are discussed in detail. After the IS impacts the perturbed II, the rippled RW is reflected upstream, and the rippled TS moves towards the II (121 s).…”
Section: Quasi-2-d Hydrodynamic Instabilitiesmentioning
confidence: 99%
“…The magnitude of the density-gradient field in the simulation is calculated as (Quirk & Karni 1996; Sembian, Liverts & Apazidis 2018) The numerical results are shown in the bottom half of the images in figure 3. It can be observed that both waves and interfacial morphologies in simulations qualitatively agree well with the experimental results.…”
Section: Qualitative Analysismentioning
confidence: 99%
“…The magnitude of the density-gradient field in the simulation is calculated as (Quirk & Karni 1996;Sembian, Liverts & Apazidis 2018)…”
Section: Qualitative Analysismentioning
confidence: 99%